A Theory of the Merging Noospheres: Teilhard and Big History. Issue 1 (2nd January 2022) - Campa, Riccardo; Corbally, Christopher; Rappaport, Margaret Boone
ABSTRACT: As the number of detected Earth-like exoplanets keeps increasing, the prospect of contact with extraterrestrial civilizations becomes day after day more plausible. It has been noticed that the encounter between space civilizations implies a fusion of Big Histories. By following Teilhard, the authors argue that the hypothetical contact with alien intelligent life would also result in a merging of the noospheres. The long-term perspective of this process is the awakening of the entire universe. This article provides a history of the idea of noosphere, a reconstruction of Teilhard's "sociological theory, " and an exploration of the theological consequences of his theory.